Rancang Bangun Sistem Penyiraman Nutrisi Otomatis Berbasis ESP32 dan IoT Blynk untuk Kebutuhan Tanaman Selada Hidroponik Drip - Muhammad Fikri Mubarak; Nadira Alfiyantika; Jeki Parlindungan Simarmata; Eka Dodi Suryanto; Dian Putri Saragih (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research aims to design and build a prototype of an automatic nutrient irrigation system for hydroponic lettuce plants using the drip method based on ESP32 and the Internet of Things (IoT) using the Blynk platform. The system monitors pH, Total Dissolved Solids (TDS), temperature, humidity, water level, and nutrient flow volume using a 4502C pH sensor, a TDS Meter V1.0 sensor, a DHT11 sensor, an HC-SR04 ultrasonic sensor, and a YF-S201 water flow sensor. The system also utilizes a DS3231 RTC module as an accurate time reference. Nutrient irrigation is carried out automatically at a volume of 340 mL per cycle based on a time schedule. The system is designed to monitor pH (6–7), nutrient concentration (TDS) (560–840 ppm), and solution capacity in the reservoir (>20%). When parameters fall outside the specified limits, the system will trigger an alarm via a buzzer and send real-time notifications to the user via the Blynk platform. The DHT11 sensor is used to classify environmental conditions so that watering intervals can be adjusted adaptively. Furthermore, the system utilizes the Non-Volatile Storage (NVS) feature on the ESP32 to store the last watering data to maintain system consistency after a power outage or restart. The system also features a push button as a reset button to re-initialize the system. Test results show that the pH, TDS, and ultrasonic sensors have error rates of 0.65%, 1.48%, and 0.83%, respectively. The system is capable of precisely controlling watering volume using the YF-S201 water flow sensor. The system can still operate optimally offline without relying on an internet connection. Thus, the developed system can improve the efficiency, accuracy, and reliability of drip hydroponic lettuce nutrient irrigation.